A Synthesis of Furan-2-iminophosphoranes under Appel-Type Reaction Conditions - Yavari, Issa; Saffarian, Hamed; Khaledian, Omid (Synlett, 2022)
Phenacylmalononitriles reacted with triphenylphosphine and carbon tetrachloride in an Appel-type, cyclization/aromatization reaction to afford 5-aryl-2-[(triphenylphosphoranylidene)amino]-3-furonitriles in yields of 75–92%. The reaction proceeded smoothly in the presence of excess amounts of Ph3P and CCl4 without any base or catalyst at room temperature. The structure of one product was confirmed by X-ray crystallographic analysis.
Keywords: Appel reaction; iminophosphoranes; triphenylphosphine; furanimines; acylmalononitriles